2022
DOI: 10.1039/d2ra03160d
|View full text |Cite
|
Sign up to set email alerts
|

Structure and surface analyses of a newly synthesized acyl thiourea derivative along with its in silico and in vitro investigations for RNR, DNA binding, urease inhibition and radical scavenging activities

Abstract: A new acyl thiourea derivative was explored for its binding interaction with RNR and DNA and for excellent urease inhibition activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Individual absorption and emission spectra and the cyclic voltammogram of each compound (UP–1-3) were recorded for their optimized concentration (2 × 10 −5 M). Then DNA titrations, upon the compound’s fixed concentration, were carried out in spectrophotometric (UV-visible and fluorescence) and cyclic voltametric (CV) experiments using DNA concentrations ranging from 10 to 70 μM at pH (7.0) and at physiological temperature of 37 °C [ 51 ]. The cells used in these experiments were kept at rest for a few minutes before each run to assure an equilibrium for the compound–DNA complex.…”
Section: Methodsmentioning
confidence: 99%
“…Individual absorption and emission spectra and the cyclic voltammogram of each compound (UP–1-3) were recorded for their optimized concentration (2 × 10 −5 M). Then DNA titrations, upon the compound’s fixed concentration, were carried out in spectrophotometric (UV-visible and fluorescence) and cyclic voltametric (CV) experiments using DNA concentrations ranging from 10 to 70 μM at pH (7.0) and at physiological temperature of 37 °C [ 51 ]. The cells used in these experiments were kept at rest for a few minutes before each run to assure an equilibrium for the compound–DNA complex.…”
Section: Methodsmentioning
confidence: 99%
“…The crystallographic data of synthesized compound 3 was collected by a diffractometer (Rigaku Oxford Diffraction Xcalibur, Eos, Gemini) equipped with Cu K α radiation ( λ = 1.54184 Å). The same methodology was employed as reported in our previous study ( Khalid et al, 2022 ). The detailed methodology for crystallographic data analysis is given in supplementary data.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported the N-((4-acetylphenyl) carbamothioyl)-2,4-dichlorobenzamide derivative ( Figure 1 ) as a possible urease inhibitor based on experimental and computational studies ( Khalid et al, 2022 ). The present work aims to investigate N-((4-acetylphenyl)carbamothioyl) pivalamide 3) as a multi-targeted chemical that might be exploited as a drug-like contender in the future.…”
Section: Introductionmentioning
confidence: 99%
“…5). 68 Two novel acyl thiourea N-benzoyl-N 0 -(4-cyanophenyl)thiourea (45) and N-(4-nitrobenzoyl)-N 0 -(4-cyanophenyl)thiourea (46) were synthesized and their structure was determined by single crystal XRD analysis, it was found that the compound (45) crystallized in triclinic crystal system adopting P 1 space group. Crystal packing of the molecules crystal was stabilized by intramolecular C]O/H-N hydrogen bond and intermolecular C]S/H-N and C]S/H-C hydrogen interactions (Fig.…”
Section: Molecular and Crystal Structurementioning
confidence: 99%
“…Baitullina et al synthesized 2,6-dipicolinoylbis(N,N-dialkylthioureas) (174a and 174b) based heterometallic gold metallacages as a platform for the development of nuclear medicine for different (radio)nuclides such as 68 Ga, 177 Lu, and 198 Au. Synthesized metallacages were also screened for their anticancer activity against MCF-7, PC-3, U383 and U343 and it was found that the IC 50 values of metallacages are comparable to auranon.…”
Section: Metallacagesmentioning
confidence: 99%